Pelaksanaan Program Dakwah dan Pemberdayaan Santri Pondok Pesantren Hataska Semurup Kerinci-Jambi - Dedi Iria Putra (Jurnal Dakwah dan Komunikasi, 2017)
Pondok Pesantren as an educational institution that develop spiritual and life skills. One of them Pondok Pesantren Hataska. The problem in this research is what is the program of empowering students of Pondok Pesantren Hataska Semurup Kerinci-Jambi. How the implementation of empowerment program students of boarding school Hataska Semurup Kerinci-Jambi regency. There are five basic concepts of da'wah and the development of Islamic society 1. Ukhuwah (the importance of unity to gain strength) 2. Ta'awun (the inter-team approach in community development) 3. 'Amilun (a group with enough skills) 4. Ma'rifah (cultural understanding of society) 5. Yaqin have the ability to be independent). Pesantren is an institution that combines formal and non formal education that prioritizes the practice of Islamic values that become the daily lifestyle, with the development of pesantren also preparing santri in the field of life skill so as to adapt well when returning to society. In the implementation of empowerment program students of Hataska Pondok Pesantren in the field of spiritual and life skill implemented three stages: first, the giving of material. Second, training. Third, the implementation.